Europe in the Age of Post-Truth Politics Populism, Disinformation and the Public Sphere - Conrad, Maximilian; Hálfdanarson, Guðmundur; Michailidou, Asimina; Galpin, Charlotte; Pyrhönen, Niko (Palgrave Studies in European Political Sociology, 2023)
This open access book is the product of three years of academic research that has been carried out in the EU-funded Jean Monnet Network on "Post-Truth Politics, Nationalism and the Delegitimation of European Integration" since 2019. Drawing on the multidisciplinary expertise of the network's members, the book explores the impact of the phenomenon of post-truth politics on European integration and the European Union. It places particular emphasis on how post-truth politics has played out in the public sphere and asks what impact the phenomenon has had on public deliberation, but reflects also on its implications for democracy in a wider sense. This book is primarily written for audiences with an interest in politics and policy making, including academics, policy makers and civil-society actors. Thanks to its accessible style, the book should however also be an asset to wider audiences.